2018
DOI: 10.1177/1464420718802464
|View full text |Cite
|
Sign up to set email alerts
|

The effect of molybdenum on titanium’s castability in dental prosthesis applications: A numerical analysis

Abstract: The ISO 22674 standard categorizes metallic materials that are suitable for dental appliances and restoration fabrication. Nickel, cadmium, and beryllium are classified as hazardous elements in this international standard. However, many alloys containing nickel and beryllium are used in dentistry as biomedical metallic materials. Numerous studies on the toxicity of nickel and beryllium have led to serious doubts about the biological reliability of these alloys. Titanium therefore attracts great interest due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…For example, low pH, high concentration of fluoride (dental implants) and the presence of oxidizing agents are considered as the main factors inducing corrosion [ 28 , 29 , 30 ]. Moreover, it has been found that the toxicity of titanium alloys depends on the alloy composition [ 16 , 31 , 32 , 33 , 34 , 35 ], and thus the careful selection of the material should be performed [ 18 ]. The first-generation titanium alloys, which contain Cr, Ni, Be and Co, are very toxic, whereas those with Al and V exhibit little toxicity and slight allergic effects.…”
Section: Toxicity Of Titanium and Its Alloysmentioning
confidence: 99%
“…For example, low pH, high concentration of fluoride (dental implants) and the presence of oxidizing agents are considered as the main factors inducing corrosion [ 28 , 29 , 30 ]. Moreover, it has been found that the toxicity of titanium alloys depends on the alloy composition [ 16 , 31 , 32 , 33 , 34 , 35 ], and thus the careful selection of the material should be performed [ 18 ]. The first-generation titanium alloys, which contain Cr, Ni, Be and Co, are very toxic, whereas those with Al and V exhibit little toxicity and slight allergic effects.…”
Section: Toxicity Of Titanium and Its Alloysmentioning
confidence: 99%